Edukasi Pentingnya Vaksinasi Covid-19 Melalui Program Kemitraan Masyarakat Pada Kolom 13 GMIM Siloam - Edy, Hosea Jaya; Suoth, Elly Juliana (Universitas Sam Ratulangi, 2021)
The global pandemic caused by the corona virus is still ongoing and continues to cause casualties. The Indonesian government has carried out a COVID-19 vaccination program for citizens to prevent the spread of the corona virus. The program that has been carried out in this activity has provided information and education about the importance of the covid-19 vaccination program. The education that has been provided includes information that the covid-19 vaccine used is safe and halal. The public has been educated that the covid-19 vaccination is very important in the process of increasing the body's immunity against the corona virus. Activities were conducted for the community in column 13 of GMIM Siloam, Sosonopan, Paniki with the method of educational information campaign. Public knowledge that the COVID-19 vaccine is safe and halal will increase after receiving education so that they are willing to participate in the vaccination program. Keywords: Virus; corona; vaccine; safe; halal AbstrakPandemi global yang disebabkan oleh virus corona masih berlangsung dan terus menimbulkan korban jiwa. Pemerintah melakukan program vaksinasi covid-19 kepada masyarakat Indonesia untuk mencegah penyebaran virus corona. Program yang dilakukan dalam kegiatan ini adalah memberikan informasi dan edukasi tentang pentingnya program vaksinasi covid-19. Edukasi meliputi informasi bahwa vaksin covid-19 yang digunakan aman dan halal. Masyarakat juga diedukasi bahwa vaksinasi covid-19 sangat penting dalam proses peningkatan kekebalan tubuh terhadap virus corona. Kegiatan dilakukan terhadap masyarakat kolom 13 GMIM Siloam, Sosonopan, Paniki dengan metode kampanye informasi edukasi (KIE). Pengetahuan masyarakat bahwa vaksin covid-19 aman dan halal akan meningkat setelah mendapat edukasi sehingga bersedia mengikuti program vaksinasi.Kata kunci: Virus; corona; vaksin; aman; halal